Transboundary movements of foot-and-mouth disease from India to Sri Lanka: A common pattern is shared by serotypes O and C. - L T Ranaweera; W W M U K Wijesundara; H S M Jayarathne; N J Knowles; J Wadsworth; A Gray; A M J B Adikari; C K Weebadde; S D S S Sooriyapathirana (PLoS ONE, 2019)
Foot-and-mouth disease (FMD) affects the livestock industry in a transboundary manner. It is essential to understand the FMD phylodynamics to assist in the disease-eradication. FMD critically affects the Sri Lankan cattle industry causing substantial economic losses. Even though many studies have covered the serotyping and genotyping of FMD virus (FMDV) in Sri Lanka, there is a significant knowledge gap exists in understanding the FMDV phylodynamics in the country. In the present study, the VP1 genomic region of FMD viral isolates belonging to serotype C from Sri Lanka and other South Asian countries were sequenced. All the published VPI sequences of serotype C and most of the published VP1 sequences for lineage ME-SA/Ind-2001d of serotype O from Sri Lanka, India, and other South Asian countries were retrieved. The datasets of serotype C and serotype O were separately analyzed using Bayesian, maximum likelihood, and phylogenetic networking methods to infer the transboundary movements and evolutionary aspects of the FMDV incursions in Sri Lanka. A model-based approach was used to detect any possible recombination events of FMDV incursions. Our results revealed that the invasions of the topotype ASIA of serotype C and the lineage ME-SA/Ind-2001d have a similar pattern of transboundary movement and evolution. The haplotype networks and phylogenies developed in the present study confirmed that FMDV incursions in Sri Lanka mainly originate from the Indian subcontinent, remain quiet after migration, and then cause outbreaks in a subsequent year. Since there are no recombination events detected among the different viral strains across serotypes and topotypes, we can assume that the incursions tend to show the independent evolution compared to the ancestral viral populations. Thus, we highlight the need for thorough surveillance of cattle/ruminants and associated product-movement into Sri Lanka from other regions to prevent the transboundary movement of FMDV.